Association between BMI, Blood Pressure, and Age: Study among Tangkhul Naga Tribal Males of Northeast India. (25th December 2011) - Mungreiphy, N. K.; Kapoor, Satwanti; Sinha, Rashmi
Abstract : Purpose . To find the prevalence of overweight/obesity and hypertension, and to study the association between BMI, blood pressure, and age. Methods . Cross-sectional study was carried out among 257 Tangkhul Naga males of Northeast India, age ranging from 20–70 years. The subjects were divided into five different age groups to study age trend. Results . Mean systolic, and diastolic BP was higher among subjects with elevated BMI and among older subjects. Minimum BP was found among underweight and maximum among obese. BP was found lowest among the youngest age group and higher among the elderly subjects. BMI was also found to be associated with age independently. Although the magnitude of correlation differed, there was significant positive correlation among BMI, age, systolic and diastolic BP. Odd ratios showed overweight/obese subjects to be more likely to have hypertension than those with normal BMI. Changing socioeconomic environment intensifies the prevalence of overweight/obesity and hypertension among the Tangkhul Nagas.